1998
DOI: 10.1016/s1085-5629(98)80005-9
|View full text |Cite
|
Sign up to set email alerts
|

Unusual cutaneous malignancies

Abstract: The most commonly occurring cutaneous malignancies are basal cell and squamous cell carcinoma. There are, however, other rare malignancies that are encountered and should be included in the differential, in which both the clinical and the histological diagnosis may be difficult. Here, the clinical and histological features, management, and prognostic factors of merkel cell carcinoma, microcystic adnexal carcinoma, leiomyosarcoma, dermatofibrosarcoma protuberans, and angiosarcoma are reviewed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
28
1

Year Published

2000
2000
2011
2011

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(30 citation statements)
references
References 107 publications
1
28
1
Order By: Relevance
“…1 To our knowledge, this study of 48 patients is the largest MAC case series reported in the literature. Although previous literature reviews 10,11,[17][18][19] helped physicians understand the epidemiological features of MAC, diagnostic criteria were not standardized, and thus comparison between series is potentially problematic. We benefited from having all specimens reviewed by the same 2 senior dermatopathologists.…”
Section: Commentmentioning
confidence: 99%
See 1 more Smart Citation
“…1 To our knowledge, this study of 48 patients is the largest MAC case series reported in the literature. Although previous literature reviews 10,11,[17][18][19] helped physicians understand the epidemiological features of MAC, diagnostic criteria were not standardized, and thus comparison between series is potentially problematic. We benefited from having all specimens reviewed by the same 2 senior dermatopathologists.…”
Section: Commentmentioning
confidence: 99%
“…The female predominance that was evident in our study has been observed, albeit inconsistently, in other series. 14,[18][19][20]23,24 Again, women also appeared to be affected at an older age than men. This age-sex interaction seems to be common among other adnexal neoplasms, especially syringomas and trichoblastomas.…”
Section: Commentmentioning
confidence: 99%
“…Our findings did not support those of others who have documented that 20% of lesions were located in the eyelid or perioral region. 28,29 We added one additional patient with MCC of unknown primary site to the few documented cases already in the literature. [30][31][32][33] MCC without a primary tumor location can be a diagnostic dilemma for the surgical pathologist because of its histologic similarities with poorly differentiated small cell and other neuroendocrine carcinomas.…”
mentioning
confidence: 99%
“…The tumor can be mistaken for other neoplasms, such as squamous cell carcinoma [7,12,13,21] as in the first biopsy of our patient. There is a relationship of MAC with salivary and sweat gland tumors [60], since they share common histological features and chromosomal aberrations.…”
Section: Discussionmentioning
confidence: 73%